Agricultural intensification and risk in water-constrained hard-rock regions: a social-ecological systems study of horticulture cultivation in western India - Pooja Prasad (Resilience Alliance, 2020)
Developing countries frequently find their poverty reduction initiatives to be at odds with promotion of sustainable practices. In India too, agricultural intensification through horticulture cultivation is an important government strategy to raise farm incomes but its mechanisms and implications have not been critically analyzed. Our objective is to characterize this intensification and explore conditions under which its goals may be achieved while ensuring equity in access to ecological services and resilience of the social-ecological system (SES). Our focal SES is the water-constrained farm system of western India that overlays shallow hard-rock aquifers common to the Indian peninsula. We document farm decisions and coping strategies of 121 farmers over two consecutive years: a drought year and a good rainfall year. We find that farmers are driven to high-value horticulture to remain economically viable in the face of increasing social-ecological vulnerability due to factors such as monsoon variability, high groundwater development, and uncertainty in irrigation access. Through systems modeling, we uncover the feedback loops that propagate risk. Risk in access to water, in part due to monsoon dry spells, starts a cycle of expensive investments often requiring large loans to assure access and a simultaneous move to horticulture in response to the elevated cost of water. This mitigates risk for the farmer in the short run but, in the absence of regulation and complete information about the common groundwater pool, leads to competitive investments, driving the regime to greater uncertainty levels for the entire community. This vicious cycle of investment and intensification escalates risk, leading to frequent crop failure, farmer indebtedness, and the tragedy of the commons. Government interventions further catalyze this. We propose alternate leverage points to enhance social comprehension of risk and facilitate collective action so as to negotiate room for human needs while remaining within biophysical boundaries.